Adult pedestrian traffic trauma in Cape Town with special reference to the role of alcohol - Peden, Margaret Mary (Department of Surgery, 2017)
This research is a prospective, descriptive survey of adult pedestrian injuries in Cape Town. It profiles 'at risk' pedestrians and describes their injuries, injury severity and outcome. The role which alcohol plays in these collisions is threaded through the thesis. Since no study of this nature has been done in South Africa, it provides baseline data on the epidemiology, alcohol-relatedness, clinical presentation and prevention of adult pedestrian collisions in the metropole. Data were collected prospectively on all injured pedestrians who presented consecutively, within six hours of being injured, to the Trauma Unit of Groote Schuur Hospital over a nine week period in 1993. Data were also gathered retrospectively from the state mortuary on all pedestrians who died before reaching hospital during the same time period. A total of 227 patients were included in the study. Data gathered included demographics, physiological response to injury, anatomical nature and severity of injuries as well as progress and outcome. Injuries were assessed and scored using the Abbreviated Injury Score (1990 revision) and the New Injury Severity Score. Alcohol consumption was assessed using four measures, viz. self-evaluation, clinical assessment, breath alcohol analysis and blood alcohol concentration (SAC). Data were analysed using SAS version 6. The study recorded a very high incidence of alcohol intoxication among injured pedestrians in Cape Town. This is highly suggestive of a causal link. One hundred and forty-one patients (62.1%) were found to have positive BACs; more than 40% had BACs in excess of 0.20 g/100ml. SAC positive pedestrians were found to have more severe injuries, to require longer hospitalisation periods and to need more complex management. They consequently cost more to treat than their sober counterparts. The comparison between the four methods of alcohol assessment revealed that self-evaluation and clinical assessment were poor screening tools. Breath alcohol analysis, using a Lion Alcolmeter S-D2, had a high degree of accuracy when compared to the SAC, which remains the 'gold standard'. It is therefore recommended that all traffic trauma patients be subjected to breath analysis. The study also generated recommendations for the prevention of pedestrian collisions. These address pre-crash, crash and post-crash factors. Control of drunken driving and walking, as well as road safety education, particularly to pedestrians, are key issues. However, there remains a need for improved road engineering and better monitoring of the roadworthiness of vehicles. This thesis highlights the severity of alcohol-related pedestrian injuries and the importance of preventative strategies.